2015
DOI: 10.17096/jiufd.86392
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Dental Anomalies in a Turkish Population

Abstract: Purpose:The aim of the present study was to investigate the prevalence of dental anomalies in a Turkish population according to the gender and age.Materials and Methods:A retrospective study was performed using panoramic radiographs of 2025 patients (885 males and 1140 females) ranging in age from 9 to 35 (mean age 25.61±10.04) years attending Department of Oral Radiology, University of Istanbul, Faculty of Dentistry. These patients were examined to determine the presence of developmental dental anomalies invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
1
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 25 publications
3
11
1
10
Order By: Relevance
“…[ 27 ] The finding that maxillary laterals were most frequently missing in the arch was consistent in the previous studies that excluded third molars. [ 4 7 9 12 28 29 55 ] Interestingly, in contrast to previously reported, the incidence of missing mandibular laterals is most significant in our study. This study also deduced that agenesis is of higher occurrence in the mandibular arch, contradictory to the findings among the Iranian populations, wherein more missing teeth were found on the maxillary arch.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…[ 27 ] The finding that maxillary laterals were most frequently missing in the arch was consistent in the previous studies that excluded third molars. [ 4 7 9 12 28 29 55 ] Interestingly, in contrast to previously reported, the incidence of missing mandibular laterals is most significant in our study. This study also deduced that agenesis is of higher occurrence in the mandibular arch, contradictory to the findings among the Iranian populations, wherein more missing teeth were found on the maxillary arch.…”
Section: Discussioncontrasting
confidence: 99%
“…In studies conducted within the past 6 years, the prevalence ranged from 4.74 to 45.1%. [ 4 7 8 9 10 11 12 13 ] These variations are most likely due to the sampling technique, subject's inclusion criteria, and the study design. Unlike other researches which assessed the radiographs and dental records alone, this study was supplemented by the subjects’ study cast.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…En el presente estudio, la frecuencia de supernumerarios estuvo dentro del rango reportado: 4,5%; al igual que el 5% citado en una investigación en Costa Rica en el 2009 (17), o un 3,6% reportado en un estudio en Colombia en el 2014 (2). Dichas frecuencia son altas si se comparan con estudios en España (4), Turquía (22), Australia (23) e India (24) donde la frecuencia de supernumerarios fue inferior al 1%.…”
Section: Discussionunclassified
“…4,[7][8][9] The most common dental anomalies in Turkish population is said to be hypodontia. 10 In Turkey, studies showed that the frequency of hypodontia were found between %1.77-%21.6, 11,12 the prevalence of oligodontia were found to be between %0.13-%0.3. 10,13 The most commonly missing teeth were found to be maxillary lateral incisors and followed by mandibular second premolars.…”
Section: Introductionmentioning
confidence: 98%